Evaluation of refractive, tomographic and biomechanical changes after customized accelerated corneal collagen cross-linking in keratoconus patients: a retrospective observational study - Robert Edward T. Ang; Alvin Joseph A. Guloy; Emerson M. Cruz; Jimmy Jarvis Gene C. Lo (BMC Ophthalmology)
Abstract Objective To evaluate the refractive, keratometric, and biomechanical changes in keratoconus patients following modified accelerated corneal cross-linking (A-CXL). Methods This retrospective observational study analyzed clinical data from patients with progressive keratoconus who underwent modified A-CXL with a prolonged riboflavin imbibition period prior to UV irradiation. Preoperative and post-operative data on vision, refraction, tomography using OCULUS Pentacam and biomechanics using Corvis ST were analyzed at various follow-up intervals. Subgroup analysis was conducted based on topographic keratoconus classification. Statistical comparison was performed to assess changes in these parameters over time. Results A total of 70 eyes of 55 patients were included. A statistically significant improvement in mean change of logMAR BCVA was noted at 6 and 12 months (p = 0.006 and p = 0.018). Six months following A-CXL, statistically significant improvements were observed in keratometry and pachymetry (p = 0.003 and p < 0.001). Mean changes in biomechanical parameters deformation amplitude ratio (DAR) and Integrated Radius (IR) were found to be significantly decreased at 6 months (p = 0.001 and p = 0.011). Other biomechanical parameters SPA1, SSI and ARTh had no significant changes suggesting stability. Comparative analysis between different stages of keratoconus revealed that patients classified under TKC-4 exhibited greater improvement in keratometry compared to those with TKC-2 and TKC-3 staging. Conclusion A-CXL with extended riboflavin exposure was effective in stabilizing both tomographic and biomechanical parameters which resulted in increased corneal stiffness and maintained stability. All KC stages demonstrated corneal stability following A-CXL.